Experiential knowledge of expert coaches on the critical performance factors of the taekwondo roundhouse kick. Issue 3 (June 2023) - Bercades, Luigi T.; Oldham, Anthony R.H.; Lorimer, Anna; Lenetsky, Seth; Millar, Sarah Kate; Sheerin, Kelly
The primary aim of this study was to capture expert taekwondo coaches' experiential knowledge regarding critical factors that underpin the roundhouse kick. The secondary aim was to explore the coaching–biomechanics interface and translate the coaches' knowledge into observable biomechanical variables for future investigation. The final aim was to elicit further expert knowledge to assess the usefulness of the resulting variables. Six higher themes emerged from interviews involving four coaches: (1) hip flexibility, (2) balance, (3) control/coordination, (4) distance, (5) footwork and (6) speed. These were supported by several sub-themes. The authors translated each theme and sub-themes into biomechanical variables: (1) front knee height, (2) support foot balance, (3) foot velocity, (4) interpersonal distance and (5) cut-kick transition speed. Two separate expert coaches appraised these variables in terms of understanding, importance, coachability and differences in expertise. In attempting to translate expert knowledge to biomechanical variables, we supported the need for a common conceptualisation of knowledge between scientists and coaches.